2002
DOI: 10.1016/s0028-3932(01)00202-0
|View full text |Cite
|
Sign up to set email alerts
|

Categorisation of ‘perceptual’ and ‘premotor’ neglect patients across different tasks: is there strong evidence for a dichotomy?

Abstract: The aim of the presented studies was to investigate whether classifications of neglect patients into perceptual (i.e. identifying a patient as suffering from mainly attentional/space representation deficits) and premotor (judging the main impairment to be related towards actions into contralesional space) categories is consistent across different line bisection assessment techniques that have, in the past, been designed to tease these potentially overlapping aspects of hemispatial neglect apart.Twelve patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
30
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 33 publications
4
30
0
1
Order By: Relevance
“…This pattern suggests important functional differences between bisection and landmark tasks, consistent with dissociations between these tasks reported both in neuropsychological patients (e.g., Harvey et al, 2002;Ishiai et al 1998) and healthy adults (e.g., Varnava, Dervinis, & Chambers, 2013). The meta-analysis of Jewell and McCourt (2000) found much larger effect sizes for pseudoneglect measured using landmark than manual (overt) bisection.…”
Section: Differences Between Landmark and Bisection Taskssupporting
confidence: 70%
“…This pattern suggests important functional differences between bisection and landmark tasks, consistent with dissociations between these tasks reported both in neuropsychological patients (e.g., Harvey et al, 2002;Ishiai et al 1998) and healthy adults (e.g., Varnava, Dervinis, & Chambers, 2013). The meta-analysis of Jewell and McCourt (2000) found much larger effect sizes for pseudoneglect measured using landmark than manual (overt) bisection.…”
Section: Differences Between Landmark and Bisection Taskssupporting
confidence: 70%
“…Harvey, Kramer-McCaffery, Dow, Murphy, and Gilchrist (2002) reported data from subjects with neglect tested on three tasks: the overhead task (Nico, 1996), the pulley test (Bisiach, Geminiani, et al, 1990), and the landmark test (Milner, Brechmann, & Pagliarini, 1992) known to distinguish between sensory-attentional and motor-intentional neglect; they found that the same patients were not consistently classified with these measures. Furthermore, there is only preliminary evidence, in one case study, that subtype-defined patterns of performance are stable across time (Barrett, Crucian, Schwartz, & Heilman, 1999).…”
Section: Neglect Is a Heterogeneous Disordermentioning
confidence: 99%
“…If a task requires a directional motor response (like line bisection or item cancellation tasks do) then perceptual and motor effects may be confounded (Bisiach et al, 1990;Bisiach, 1993); an error could reflect an impairment in orienting visual attention towards contralesional space or in making movements towards such locations. Much research has been conducted to try and dissociate the contribution of perceptual and motor effects (Bisiach et al, 1990;Harvey et al, 2002a), and various tasks have been designed to try and overcome this confounding such as landmark and pulley device tasks (see Harvey, 2004 for a review). We feel that it is important to examine perceptual visuospatial processes using a task that does not rely on a potentially confounding motor response, and visual search is one such task.…”
Section: Introductionmentioning
confidence: 99%